S08-2: Monitoring Physical Activity Policies at the Subnational Level: A Review of Existing Tools (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The subnational level plays a key role in physical activity (PA) promotion, e.g. by developing policies across different sectors and/or by implementing national PA policies. However, research on PA policy monitoring focuses mainly on the national level; to close this gap, new monitoring tools have been developed that are specifically designed for the local or regional level. This study aimed to identify and examine existing PA policy monitoring tools for the subnational level and to determine their key elements.Methods: As PA policy monitoring tools developed by governments are not necessarily described in scientific studies, a systematic grey literature review was conducted. Steps included: (1) reference screening of existing reviews, (2) grey literature search in the data bases OpenGrey and Startpage, and (3) expert consultation. Tools were included if they were focused on the subnational level and PA policies. Key characteristics of the tools were extracted and analysed systematically (e.g. scope, data sources, scale, method of data collection, number of items, content).Results: This review identified 17 tools that monitor, assess, or benchmark PA policies at sub-national level. Preliminary results indicate that nine of these tools were developed by researchers, while eight can be described as government-driven. The methodology of data collection differs; while the majority of tools are based on surveys, some utilise desk-research in combination with expert consultation. Most tools were tested in a single country. Moreover, the number of indicators varied widely, from as few as eight to over 280.Conclusion: The review identified a considerable variation in methodological approaches for subnational PA policy monitoring, from in-depth qualitative case studies to large scale nationwide surveys that take place on a regular basis. As many tools were developed in a specific national context, their transferability to other countries is often unclear.Support/Funding Source: This is part of the project IMPAQT, which is funded from Ireland, Health Research Board; Poland, National Centre for Research and Development; Germany, Federal Ministry of Education and Research; The Netherlands, The Netherlands Organisation for Health Research and Development; Romania, Executive Agency for Higher Education, Research, Development and Innovation Funding; Lithuania, Research Council of Lithuania, under the umbrella of the Partnership Fostering a European Research Area for Health (ERA4Health) (GA N° 101095426 of the EU Horizon Europe Research and Innovation Programme).